Language and ritual gesture in the Andean South - Urbano, Henrique Osvaldo (1976)
During several months of the year 1974, we collected some interviews in Quechua about rites and rituals of the Andean South. The cases that we transcribe directly from Quechua today are part of longer interviews. We selected only some parts of the interview, focusing mainly on questions of vocabulary and ritual gestures.